2018
DOI: 10.3390/electronics7090178
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Power Transfer for Battery Powering System

Abstract: The LCL topology (formed by an LC tank with a transmitting coil) is extensively utilized in wireless power transfer (WPT) systems with the features of a constant resonant current and ability to disconnect load abruptly. However, it requires high input voltage, which limits its utilization in battery powering scenarios (12~24 V). A current-fed inverter (CFI) is applied to the LCL-S (a compensation capacitor in series with the receiving coil) WPT systems to boost the input voltage, thereby getting a higher reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…An impedance analyzer is used to extract the parameters in Eqs. (7) and (8). The original resonant frequency is set to 85.0 kHz.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An impedance analyzer is used to extract the parameters in Eqs. (7) and (8). The original resonant frequency is set to 85.0 kHz.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to the wired charging mode of EVs, the convenience of wireless charging using magnetic resonance can make EVs more acceptable to drivers because they do not need to handle power plug. At the same time, EVs system using wireless charging mode can be safer [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the first pulses these modes end, and circulation modes start. In circulation modes pulses continue to flow through the load [18].…”
Section: Control Of Power Through Harmonic Componentsmentioning
confidence: 99%
“…At the end of the first pulses these modes end, and circulation modes start. In circulation modes pulses continue to flow through the load [18]. Figure 8 shows the output voltage waveforms of the H-bridge (v bri ) and its harmonic components.…”
Section: Control Of Power Through Harmonic Componentsmentioning
confidence: 99%
“…[10] showed that magnetic resonant coupling WPT normally works in megahertz and its efficiency is improved with increasing frequency. Despite its long-lasting popularity, using coils to achieve WPT through high-frequency actions cannot satisfy today's needs, and power electronics elements are being developed to realize the same function [11]. However, it is well known that current power electronics technologies cannot satisfy such high-frequency switching [12]; therefore, in order to meet the capability of contemporary power switches to realize WPT, it is of great necessity to propose new methods for reducing the resonant frequency.…”
Section: Introductionmentioning
confidence: 99%